Non-aqueous electrolyte solution for lithium ion secondary battery and lithium ion secondary battery using same

By adding five-membered cyclic phosphate compounds and DOX to the nonaqueous electrolyte of lithium-ion secondary batteries, the problem of insufficient corrosion resistance and cycle life of the battery at high voltage or high temperature is solved, and higher battery performance and safety are achieved.

CN119585903APending Publication Date: 2025-03-07AIR WATER PERFORMANCE CHEM INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380051330.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-01
Filing Date
2023-06-01
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries show poor corrosion resistance and cycle life at high voltages or high temperatures, making it difficult to meet the high performance requirements of electric vehicles and other applications.

Method used

A nonaqueous electrolyte is used, which contains 0.01 to 10% by weight of the five-membered cyclic phosphate compound, and if necessary, 1,3-dioxane (DOX) and other SO3-containing compounds are added to improve the cycle characteristics and corrosion resistance of the battery.

Benefits of technology

It significantly improves the cycle life and corrosion resistance of lithium-ion secondary batteries at high voltages or high temperatures of more than 4.2V, ensuring the long-term stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585903A_ABST
    Figure CN119585903A_ABST
Patent Text Reader

Abstract

Provided are: a non-aqueous electrolyte solution for a lithium ion secondary battery, which has excellent cycle characteristics (cycle life), which are considered to be important, in an in-vehicle secondary battery for an electric vehicle or the like, and also has excellent corrosion resistance at high voltages or high temperatures exceeding 4.2 V; and a lithium ion secondary battery. A nonaqueous electrolyte solution for a lithium ion secondary battery according to the present invention is used in a lithium ion secondary battery having a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte solution obtained by dissolving an electrolyte salt in a nonaqueous solvent, the five-membered cyclic phosphate ester compound (I) is contained in an amount of 0.01-10% by weight. In the formula, R represents a-CH2C = CH group, a-CH (CH3) C = N group, a-C (CH3) 2C = N group or a-CH2CH2C = N group. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nonaqueous electrolyte for a lithium ion secondary battery which is excellent in battery characteristics such as battery cycle life and has safety such as battery corrosion resistance, and a lithium ion secondary battery using the nonaqueous electrolyte. Background Art

[0002] In recent years, lithium-ion secondary batteries (LIBs) have been continuously improved in terms of cycle life and high-temperature storage characteristics as they develop toward higher capacity and higher voltage. In automotive secondary batteries, LIBs have been used that use a lithium composite oxide containing Ni as the positive electrode active material, a graphite material or a compound containing Si as the negative electrode active material, and a non-aqueous electrolyte containing lithium bis(fluorosulfonyl)imide (LiFSI) as the aqueous electrolyte.

[0003] The current technology of LIB cathode materials for electric vehicles is developing towards a higher nickel content, and the technology of negative electrodes is developing towards a higher proportion of silicon-based materials mixed with the graphite materials used in the past. The purpose of this is to increase the overall energy density of the battery and extend the driving range of electric vehicles.

[0004] Today's electric vehicle LIBs are required to perform well in a variety of environments. Among them, performance at high temperatures is particularly important. If the battery for automotive LIBs is exposed to high temperatures due to the influence of heat from both inside and outside, the rate of gas generation due to the decomposition of the electrolyte will increase, and metal ions from the positive electrode will dissolve and precipitate at the negative electrode, causing battery performance to deteriorate.

[0005] On the other hand, if the protective coating layer in the negative electrode is thermally degraded, the highly active negative electrode surface directly contacts the solvent and discharges itself, reducing battery performance. This has the risk of causing more significant adverse effects on high-Ni positive electrodes and Si-based negative electrodes that have poor structural stability and high-temperature performance.

[0006] Patent Document 1 points out the problem that aluminum used as a positive electrode current collector of LIB may corrode if the battery is operated at a high voltage exceeding 4.2 V in a non-aqueous electrolyte solution containing an imide-based lithium salt such as LiFSI as an electrolyte.

[0007] In addition, Patent Document 2 proposes a LIB that has an excellent capacity retention rate and reduces gas generation after continuous charging by using a cyclic phosphate compound (A) such as ethylene (2-propynyl) phosphate and a lithium salt compound (B) such as LiPF6 that does not have an oxalic acid structure, a lithium salt compound (C) such as LiB(C2O4)2 (LiBOB) that has an oxalic acid structure, and a non-aqueous electrolyte containing a non-aqueous solvent.

[0008] However, this technology cannot be said to be sufficient in terms of battery characteristics such as battery cycle life and corrosion resistance when used at high voltage or high temperature.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2014-203748

[0012] Patent Document 2: Japanese Patent Application Publication No. 2015-99660 Summary of the invention

[0013] Problems to be solved by the invention

[0014] The object of the present invention is to provide a non-aqueous electrolyte for lithium ion secondary batteries and a lithium ion secondary battery having excellent cycle characteristics (cycle life) which is considered important in vehicle-mounted secondary batteries such as electric vehicles, and also excellent corrosion resistance at high voltages exceeding 4.2V or high temperatures.

[0015] Means of solving problems

[0016] The inventors of the present invention have conducted in-depth research and discovered a non-aqueous electrolyte for use in a lithium-ion secondary battery. The lithium-ion secondary battery comprises a positive electrode, a negative electrode, a separator and a non-aqueous electrolyte formed by dissolving an electrolyte salt in a non-aqueous solvent. The non-aqueous electrolyte contains a five-membered ring phosphate compound represented by the following formula (I) in a range of 0.01 to 10 weight %. By having the above structure, a non-aqueous electrolyte for a lithium-ion secondary battery can be obtained which can improve the cycle characteristics of the battery and has excellent corrosion resistance at a high voltage exceeding 4.2V or a high temperature.

[0017]

[0018] In the formula, R represents a -CH2C≡CH group, a -CH(CH3)C≡N group, a -C(CH3)2C≡N group or a -CH2CH2C≡N group.

[0019] When R of the five-membered ring phosphate compound represented by formula (I) is a -CH2C≡CH group, it is preferred that the electrolyte salt does not contain LiPF6 and LiBOB.

[0020] Furthermore, it is preferred that 1,3-dioxane (DOX, CAS RN: 505-22-6) is contained in a non-aqueous electrolyte containing a five-membered ring phosphate compound represented by the above formula (I) in a range of 0.01 to 5 weight %. By containing DOX, the cycle characteristics and corrosion resistance at high voltages or high temperatures exceeding 4.2V can be further improved. In particular, this effect is particularly significant when lithium bis(fluorosulfonyl)imide (LiFSI) is used as an electrolyte.

[0021] In addition, the non-aqueous electrolyte of the present invention may contain at least one compound containing an SO3 group selected from 1,3-propane sultone, 2-propynyl methanesulfonate and 2-cyanoethyl methanesulfonate in an amount within a range of 0.01 to 5% by weight.

[0022] The lithium ion secondary battery of the present invention is a lithium ion secondary battery having a positive electrode, a negative electrode, a separator and a non-aqueous electrolyte solution formed by dissolving an electrolyte salt in a non-aqueous solvent, characterized in that the non-aqueous electrolyte solution is the non-aqueous electrolyte solution for the lithium ion secondary battery of the present invention.

[0023] In the lithium ion secondary battery of the present invention, the negative electrode preferably contains a silicon-based oxide.

[0024] Effects of the Invention

[0025] The present invention can provide a nonaqueous electrolyte for lithium ion secondary batteries and a lithium ion secondary battery having excellent cycle characteristics (cycle life) which is considered important in secondary batteries for vehicles such as electric vehicles, and also excellent corrosion resistance at high voltages exceeding 4.2 V or high temperatures. DETAILED DESCRIPTION

[0026] The following are examples of the forms and structures of the present invention, but the present invention is not limited to these, and any invention that meets the intent described in the matters described in the claims, means for solving the problems, and effects of the invention are included in the present invention.

[0027] The non-aqueous electrolyte is composed of an electrolyte salt and a non-aqueous solvent. As an electrolyte salt, for example, a lithium salt such as LiN(SO2F)2(LiFSI) with a SO2 group, LiOSO2F with a SO3 group, LiOSO3CH3, LiOSO3C2H5 with a SO4 group, LiPF6 with phosphorus (P), and LiPO2F2 can be used. However, in the present invention, when a silicon oxide such as SiO and SiO2 is contained in a graphite material such as natural graphite or artificial graphite, it is preferred to use LiPF6 and an electrolyte salt other than LiBOB having an oxalic acid skeleton. The lithium salt can be used alone or in combination with two or more. For Li salts other than LiFSI, it is preferred to add a certain amount because it has the effect of assisting in improving the battery performance at low temperatures. As a preferred combination of these lithium salts, a combination of two kinds of lithium salts with a SO2 group: phosphorus (P), a combination of three kinds of lithium salts with a SO3 group: a lithium salt with a SO4 group: a lithium salt with phosphorus (P) is preferred. Specifically, a combination of two kinds of LiFSI:LiPO2F2 and a combination of three kinds of LiFSI:LiOSO3CH3:LiPO2F2 are more preferred. The molar ratio of LiFSI / other Li salts is preferably in the range of 100 / 0 to 1 / 99, more preferably in the range of 100 / 0 to 60 / 40, and most preferably in the range of 100 / 0 to 80 / 20. In addition, it is preferred to dissolve the total electrolyte salt in a concentration (mol / L) in the range of 0.5 to 3, more preferably in the range of 1 to 2.

[0028] As electrolyte solvent, can use five-membered ring carbonate or linear carbonate in main solvent.As five-membered ring carbonate, can preferably enumerate such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), vinylene carbonate (VC).When using linear carbonate, can preferably enumerate such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC).

[0029] These solvents can be used in one or more combinations. In the case where the lithium ion secondary battery of the present invention has a positive electrode active material containing Ni or a negative electrode active material containing Si, as a preferred combination of five-membered ring carbonates, from the viewpoint of inhibiting corrosion, preferably EC: FEC, EC: PC: FEC contain fluorinated FEC, as a preferred combination of chain carbonates, from the viewpoint of improving electrochemical characteristics in a high temperature region of more than 45° C. or a low temperature region of less than -20° C., preferably DMC: EMC, DEC: EMC contain asymmetric chain carbonates.

[0030] When using five-membered ring carbonate as the nonaqueous solvent of the nonaqueous electrolyte of the present invention, when containing chain ester (chain carbonate) in the above-mentioned five-membered ring carbonate, from the viewpoint of improving the electrochemical characteristics in the high temperature region above 45°C or the low temperature region below -20°C, about the ratio of five-membered ring carbonate and chain carbonate, preferably five-membered ring carbonate: chain carbonate=10:90~50:50 (capacity ratio), more preferably 20:80~40:60.

[0031] The non-aqueous electrolyte of the present invention contains a five-membered ring phosphate compound represented by the following formula (I) in a range of 0.01 to 10 weight %. In the formula, R represents a -CH2C≡CH group, a -CH(CH3)C≡N group, a -C(CH3)2C≡N group or a -CH2CH2C≡N group. By adding the above-mentioned five-membered ring phosphate compound, the corrosion resistance to metals such as aluminum is improved, so LiFSI (lithium bis(fluorosulfonyl)imide) with high chemical thermal stability and capable of improving battery performance at high temperatures can also be used in large quantities. In addition, as the above-mentioned five-membered ring phosphate compound, any one of the compounds in which R is a -CH2C≡CH group, the compounds in which R is a -CH(CH3)C≡N group, the compounds in which R is a -C(CH3)2C≡N group and the compounds in which R is a -CH2CH2C≡N group can be used, and a plurality of them can also be mixed and used.

[0032]

[0033] If the addition amount of the five-membered ring phosphate compound (I) is too little, the formation of the protective film of the negative electrode becomes insufficient, so the cycle characteristics are reduced, or the high temperature storage characteristics are affected. Therefore, the suitable use range is preferably 0.1 weight % or more, more preferably 0.5 weight % or more, relative to the non-aqueous solvent. In addition, the upper limit is preferably 5 weight % or less, more preferably 3 weight % or less, relative to the non-aqueous solvent.

[0034] In order to further improve the cycle characteristics and corrosion resistance of the five-membered ring phosphate compound (I) used in the present invention, the electrolyte of the present invention may contain 1,3-dioxane (DOX) as a six-membered ring ether in a range of 0.01 to 5 weight %. In this way, the cycle characteristics and the corrosion resistance at a high voltage exceeding 4.2V and / or exceeding room temperature can be simultaneously achieved at a higher level.

[0035] The reason for the preferred use of the above-mentioned DOX is only a guess, but it can be considered that when the five-membered ring phosphate compound (I) containing R=-CH2C≡CH group, -CH(CH3)C≡N group, -C(CH3)2C≡N group or -CH2CH2C≡N group is ring-opened and polymerized, DOX as a 6-membered ring ether is also ring-opened and polymerized, and a polymer adsorption layer with a strong synergistic effect is formed at the interface of the positive electrode active material and the negative electrode active material, preventing contact with the main solvent of the electrolyte. The use range of DOX is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and most preferably 0.5% by weight or more relative to the non-aqueous solvent. In addition, the upper limit is preferably 5% by weight or less, more preferably 4% by weight or less, and most preferably 3% by weight or less relative to the non-aqueous solvent.

[0036] According to the present invention, a non-aqueous electrolyte containing 0.01 to 5% by weight of 1,3-propane sultone (CAS RN: 1120-71-4), 2-propynyl methanesulfonate (CAS RN: 16156-58-4), and 2-cyanoethyl methanesulfonate (CAS RN: 65885-27-0) can be used. These compounds containing SO3 groups are preferably used from the viewpoint of improving the cycle life, but they are highly corrosive, so there are usually concerns about their use. However, the present invention can use them without damaging the corrosiveness of LIB.

[0037] As the separator used in the lithium ion secondary battery of the present invention, it is most preferred to use a separator composed of a microporous membrane (porous sheet) formed by a polyolefin material such as polypropylene and polyethylene, but a separator composed of a non-woven fabric can also be used. The porous sheet and non-woven fabric can be a single layer or a multilayer structure, and oxides such as aluminum oxide can also be coated on the surface of the separator. In order to increase the volume energy density of the battery, the thickness of the separator needs to be as thin as possible. Therefore, it is preferably less than 20 microns, and particularly preferably less than 10 microns.

[0038] As the negative electrode active material used in the lithium ion secondary battery of the present invention, in order to improve the volume energy density, it is preferred to list graphite materials such as natural graphite and artificial graphite that can reversibly absorb and release lithium ions. In addition, in order to increase the capacity, silicon-based oxides such as SiO and SiO2 can be appropriately added. When containing graphite and at least one silicon-based oxide, the weight of the silicon-based oxide in the negative electrode active material is preferably 1 to 30%, and more preferably 5 to 20%.

[0039] As a negative electrode composite agent, a slurry-like negative electrode composite agent can be formed by mixing ethylene propylene diene copolymer (EPDM), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene-butadiene copolymer (SBR), acrylonitrile-butadiene copolymer (NBR), carboxymethyl cellulose (CMC) and other binders into the negative electrode active material, and then the negative electrode material is coated on the copper foil or aluminum foil of the collector, dried, press-formed, and then heat-treated at 80°C under vacuum, for example.

[0040] Examples of the positive electrode active material used in the lithium ion secondary battery of the present invention include LiCoO2 (LCO), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2(NCM111), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), etc. In order to improve the volume energy density, NCM811 is preferably used as the positive electrode active material of the lithium composite oxide containing more than 50% Ni in atomic ratio. In addition, in order to improve rapid charge and discharge, LiMn2O4 (LMO) with a spinel structure and LiFePO4 (LFP) with an olivine structure are preferably used.

[0041] As a positive electrode composite, a slurry-like positive electrode composite can be formed by using carbon black such as acetylene black and Ketjen black, carbon nanotubes, carbon fibers, activated carbon, graphite and other well-known or commercially available conductive aids in the above-mentioned positive electrode active materials, and mixing polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVFF), copolymers of styrene and butadiene (SBR), copolymers of acrylonitrile and butadiene (NBR), carboxymethyl cellulose and other binders. The positive electrode material is then coated on aluminum foil as a collector, dried, press-formed, and then heat-treated in a vacuum, for example, at 80°C.

[0042] In the lithium ion secondary battery of the present invention, the combination of the positive electrode active material and the negative electrode active material is preferably a combination of LCO / graphite, NCM523 / graphite, NCM811 / graphite, or the like in order to increase the volume energy density.

[0043] The current collector used in the present invention is not particularly limited, but aluminum foil and copper foil are preferred. In order to further improve the permeability of the electrolyte, a porous current collector may be used.

[0044] In the present invention, there is no particular restriction on the solvent used in the binder, and various solvents can be selected according to the active material or binder used. Specifically, when PVDF is used as the binder, N-methyl-2-pyrrolidone is preferably used as the solvent, and on the other hand, when a rubber-based binder such as styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinyl alcohol, carboxymethyl cellulose (CMC) is used, water is preferably listed as the solvent.

[0045] The structure of the lithium secondary battery of the present invention is not particularly limited, and the shape of the secondary battery having a positive electrode, a negative electrode and a separator may include a coin-shaped battery, a cylindrical battery, a square battery, a pouch-shaped battery, etc. Among them, a pouch-shaped battery having excellent heat dissipation is preferred.

[0046] Example

[0047] The present invention is specifically described below with reference to Examples and Comparative Examples, but they do not limit the present invention in any way.

[0048] [Example 1-1]

[0049] [Preparation of electrolyte]

[0050] The non-aqueous electrolyte was prepared so that R=CH2CH2C≡N of the phosphate compound (I) was 1 wt% relative to 100 vol% of an electrolyte solution of 1M LiFSI PC / DMC=1 / 2 (volume ratio).

[0051] [Manufacturing of lithium secondary batteries and measurement of battery characteristics]

[0052] NCM811 (positive electrode active material) is 93% by weight, acetylene black (conductive aid) is 3% by weight, and polyvinylidene fluoride (binder) is 4% by weight. They are mixed, 1-methyl-2-pyrrolidone is added thereto to form a slurry, and applied on aluminum foil. Then, dry and press-form to form a positive electrode. Similarly, artificial graphite (negative electrode active material) is 98% by weight, a copolymer of styrene and butadiene as a binder is 1% by mass, and carboxymethyl cellulose is 1% by mass. They are added to water and mixed to form a slurry, which is applied on copper foil. Then, dry, press-form, and heat-treat to form a negative electrode sheet. Then, a 3-layer 20-micron microporous film made of polypropylene sandwiched with polyethylene is used as a separator, and the above-mentioned electrolyte is injected to make a coin battery (diameter 20 mm, thickness 3.2 mm). The results are shown in Example 1-1 of Table 1.

[0053] Using a charge and discharge device ACD-MO1A (manufactured by Aska Electronics), the coin battery was charged to an upper limit voltage of 4.3V at a constant current and constant voltage rate of 1C at 25°C, and then discharged to a lower limit voltage of 3.0V at a rate of 1C, and the charge and discharge were repeated. The discharge capacity of the 5th cycle was calculated as a relative ratio to the discharge capacity of the 5th cycle when EC / DMC=1 / 2 (capacity ratio) was used as a solvent (Comparative Example 1-2), which was 1.00. Regarding the cycle characteristics (%), it was quantified by "capacity obtained in the 50th cycle (mAh / g) / capacity obtained in the 5th cycle (mAh / g)×100". The results are shown in Example 1-1 of Table 1.

[0054] [Table 1]

[0055]

[0056] [Example 1-2 to Example 1-3, Comparative Example 1-1 to Comparative Example 1-5]

[0057] The same coin cells as in Example 1-1 were prepared except that the electrolyte composition, compound (I) and DOX used were changed as shown in Table 1, and the battery characteristics were measured. The results are shown in Table 1.

[0058] As can be seen from the results of Table 1, in a battery using a graphite negative electrode, for a PC-based electrolyte, if the non-aqueous electrolyte containing the phosphate compound (I) of the present invention is not used, the graphite negative electrode is damaged and cannot be charged and discharged satisfactorily as a secondary battery (Comparative Example 1-1, Comparative Example 1-3 to Comparative Example 1-5). In addition, it was found that by auxiliary addition of DOX described in the present invention, a synergistic effect can be obtained (Example 1-3), achieving a non-aqueous electrolyte and its LIB that are equivalent to the EC-based electrolyte (Comparative Example 1-2) in terms of initial capacity and superior to the EC-based electrolyte in terms of cycle life.

[0059] [Example 2-1]

[0060] [Determination of Corrosion Resistance]

[0061] A three-electrode beaker electrolytic cell with working electrode / counter electrode / reference electrode = Al / Li / Li was used in the measurement, and a liquid prepared by adding 2.8 wt% of the phosphate compound (I) when R = CH2CH2C≡N to 1.2M LiFSI EC / EMC / DMC = 3 / 3 / 4 (volume ratio) was used. The measurement conditions were 25°C, 5 mV / sec, 4.5-3.0 V, and the current value up to 10 cycles was determined by cyclic voltammetry (CV). Quantification was performed by "current value obtained in the 10th cycle / current value obtained in the 2nd cycle × 100%". The results are shown in Example 2-1 of Table 2.

[0062] [Table 2]

[0063]

[0064] [Example 2-2 to Example 2-3, Comparative Example 2-1 to Comparative Example 2-4]

[0065] The same three-electrode beaker electrolytic cell as in Example 2-1 was prepared except that the compounds used were changed as shown in Table 2. As the compounds used, an amount equimolar to the phosphate compound (I) when R=CH2CH2C≡N was added, and the corrosion resistance was measured. The results are shown in Table 2.

[0066] According to the results in Table 2, it can be found that by including the phosphate compound (I) in the electrolyte, the numerical value indicating corrosion resistance is greatly reduced (Example 2-1 to Example 2-2). In addition, by supplementing with DOX described in the present invention, it is found that the numerical value indicating corrosion resistance is further reduced (Example 2-3).

[0067] On the other hand, for the R portion of the five-membered ring phosphate compound (I), even if it is the same five-membered ring phosphate skeleton, in the case of R=CH2CH3 (Comparative Example 2-2) outside the scope of the present invention and R=CH2CF3 (Comparative Example 2-3) having a fluorine group, it was found that the corrosion resistance was significantly deteriorated. Therefore, it can be said that it is not all right as long as it is a five-membered ring phosphate skeleton, and a specific skeleton that does not cause graphite negative electrode damage is important.

[0068] [Example 3-1]

[0069] As the negative electrode active material, a negative electrode sheet in which SiO is added to graphite is used, and the electrolyte used, the five-membered ring phosphate compound (I), DOX, and 2-propynyl methanesulfonate as a compound containing SO3 are changed as shown in Table 3. In addition, a coin cell similar to Example 1-1 is made and the battery characteristics are measured. The negative electrode sheet is prepared as follows. 93 wt% of artificial graphite (negative electrode active material), 5 wt% of SiO (negative electrode active material), 1 wt% of a copolymer of styrene and butadiene as a binder, and 1 wt% of carboxymethyl cellulose are added to water and mixed to form a slurry, which is then applied to a copper foil. Then, it is dried, press-formed, and heat-treated to form a negative electrode sheet. In addition, a three-pole beaker electrolytic cell similar to Example 2-1 is made to measure the corrosion resistance. The results are shown in Table 3.

[0070] [Example 3-2 to Example 3-4]

[0071] The same coin cell as in Example 3-1 was prepared except that the five-membered ring phosphate compound (I) was changed as shown in Table 3, and the battery characteristics were measured. In addition, the same three-electrode beaker electrolytic cell as in Example 2-1 was prepared, and the corrosion resistance was measured. The results are shown in Table 3.

[0072] [Table 3]

[0073]

[0074] As shown in Table 3, in addition to the highly corrosive LiFSI, the corrosion resistance is also improved even for non-aqueous electrolytes containing SO4-containing compounds LiOSO3CH3, SO3-containing compounds 2-propynyl methanesulfonate, and fluorine-containing compounds FEC. Based on these results, it can be expected that even in the case of using multiple LIBs such as in-vehicle batteries, excellent cycle characteristics and corrosion resistance are maintained for a long time.

[0075] [Example 4-1, Reference Examples 4-1 to 4-6]

[0076] Using the same positive electrode active material as in Example 3-1, the same solvent as in Example 2-1, and the same five-membered cyclic phosphate compound (I) as in Example 1-2, the type of negative electrode used, the ratio of LiPF6 to LiFSI in the electrolyte, and the addition of LiBOB were changed as shown in Table 4. In addition, the same coin cells as in Example 1-1 were prepared. The battery characteristics of these coin cells were determined as follows. Using a charge and discharge device ACD-MO1A (manufactured by Aska Electronics), at 25°C, the battery was charged at a constant current and constant voltage rate of 1C to an upper limit voltage of 4.3V, and then discharged at a rate of 1C to a lower limit voltage of 3.0V, and the charge and discharge were repeated. Regarding the discharge capacity of the 5th cycle, the relative ratio compared with the discharge capacity of the 5th cycle of Comparative Example 1-2 was calculated. The cycle characteristics (%) are quantified by "capacity obtained in the 300th cycle (mAh / g) / capacity obtained in the 5th cycle (mAh / g) × 100". The results are shown in Table 4.

[0077] [Table 4]

[0078]

[0079] As can be seen from Table 4, when graphite and SiO are used for the negative electrode, the smaller the ratio of LiPF6 to LiFSI, the better the cycle characteristics (Example 4-1, Reference Example 4-1 to Reference Example 4-4). Although the cycle characteristics are good when 1wt% LiBOB is added to the LiPF6 electrolyte when only graphite is used for the negative electrode (Reference Example 4-5), in the battery using graphite and SiO for the negative electrode, even if the electrolyte with added LiBOB is used, only the cycle characteristics equivalent to or less than that of Reference Example 4-4 can be obtained (Reference Example 4-6). Based on this, it can be found that when a five-membered ring phosphate compound (I) is used in a battery in which SiO is added to the negative electrode graphite, by mainly using LiFSI as the Li salt, LiPF6 can be reduced as much as possible, and the addition of LiBOB is no longer necessary.

[0080] Industrial Availability

[0081] By using the non-aqueous electrolyte of the present invention, the battery characteristics such as the cycle characteristics of the battery are excellent, and safety such as corrosion resistance can be achieved. According to the present invention, the contribution of the present invention to the use of multiple LIBs for a long time such as in-vehicle batteries is unlimited.

Claims

1. A non-aqueous electrolyte for a lithium ion secondary battery, which is a non-aqueous electrolyte used in a lithium ion secondary battery, wherein the lithium ion secondary battery comprises a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte formed by dissolving an electrolyte salt in a non-aqueous solvent, wherein the non-aqueous electrolyte is characterized in that it contains a five-membered ring phosphate compound represented by the following formula (I) in a range of 0.01 to 10% by weight, In the formula, R represents a -CH2C≡CH group, a -CH(CH3)C≡N group, a -C(CH3)2C≡N group or a -CH2CH2C≡N group.

2. The non-aqueous electrolyte for lithium ion secondary battery according to claim 1, characterized in that The R of the five-membered ring phosphate compound represented by the formula (I) is a -CH2C≡CH group, and the electrolyte salt does not contain LiPF6 and LiB(C2O4)2.

3. The non-aqueous electrolyte for lithium ion secondary battery according to claim 1, characterized in that 1,3-Dioxane is contained in a range of 0.01 to 5% by weight.

4. The non-aqueous electrolyte solution for lithium ion secondary battery according to claim 1, wherein At least one compound containing an SO3 group selected from 1,3-propane sultone, 2-propynyl methanesulfonate and 2-cyanoethyl methanesulfonate is contained in a range of 0.01 to 5% by weight.

5. A lithium ion secondary battery comprising a positive electrode, a negative electrode, a separator and a non-aqueous electrolyte solution formed by dissolving an electrolyte salt in a non-aqueous solvent, characterized in that: The nonaqueous electrolyte solution is the nonaqueous electrolyte solution for a lithium ion secondary battery according to any one of claims 1 to 4.

6. The lithium ion secondary battery according to claim 5, characterized in that The negative electrode contains a silicon-based oxide.

Citation Information

Patent Citations

  • Nonaqueous electrolytic solution for lithium ion secondary batteries, and lithium ion secondary battery having the same

    JP2014203748A

  • Nonaqueous electrolyte and lithium ion secondary battery arranged by use thereof

    JP2015099660A